PENGARUH DEBT TO EQUITY RATIO (DER), DEBT TO TOTAL ASSET RATIO (DAR), LONG TERM DEBT TO EQUITY RATIO (LDER) DAN LONG TERM DEBT TO TOTAL ASSET RATIO (LDAR) TERHADAP PROFITABILITAS ROE PADA PERUSAHAAN FOOD AND BEVERAGES YangTerdaftar Di Bursa Efek Indonesia - Beni Prabowo; Alean Kistiyani Hegy Suryana; Milka Susana Theorupun (EKOBIS, 2022)
Research on Determined the Effect of Debt To Equity Ratio (Der), Debt To Total Asets Ratio (Dar), Long Term Debt To Euity Ratio (Lder) and Long Term Debt To Total Asets Ratyo (Ldar) Towards Profitabilty Roe In Food And Beverae Companies (Case Study In Food And Bevrage Sector Company List On The Indonesia Stock Exchange Period 2015-2019) . The population in this study were 23 companies and the sampling technique was purposive sampling method. The sample is 13 companies and obtained 65 observational data. The results that there was a positive and significant effect between DER on ROE Profitability. There was no positivie and significant effect between DAR and ROE Profitability. There is a negative and significant effect between LDER and ROE Profitability. There is no positiv and signficant effect between LDAR and ROE profitability. There is a positive and significant effect between DER, DAR, LDER, LDAR simultaneously on ROE Profitability.